Indolocarbazole based small molecules: an efficient hole transporting material for perovskite solar cells - Lim, Iseul; Kim, Eun-Kyung; Patil, Supriya A.; Ahn, Do Young; Lee, Wonjoo; Shrestha, Nabeen K.; Lee, Joong Kee; Seok, Won K.; Cho, Cheon-Gyu; Han, Sung-Hwan (ROYAL SOC CHEMISTRY, 2015)
To date, Spiro-OMeTAD, which is an expensive organic compound, has been used as the benchmark hole transporting material (HTM) in perovskite based solid state solar cells. Development of an inexpensive HTM with competitive performance to Spiro-OMeTAD is therefore significantly important for the commercialization of perovskite cells. Herein, an indolocarbazole based small molecule derivative (C12-carbazole) has been introduced as an environmentally stable, cost effective and highly efficient HTM. In contrast to the power conversion efficiency of 9.62% exhibited by the Spiro-OMeTAD based solid state solar cell, the C12-carbazole based device under the same experimental conditions has demonstrated an enhanced power conversion efficiency of 11.26%. The improved photovoltaic performance of the C12-carbazole based device is attributed to reduced carrier recombination by a better hole extraction ability of the C12-carbazole, which has demonstrated remarkably higher hole mobility compared to Spiro-OMeTAD.
Keywords: TITANIUM-DIOXIDE PHOTOANODES; CONDUCTOR